Natural Disasters : What is the Role for Social Safety Nets? - Pelham, Larissa; Clay, Edward; Braunholz, Tim (World Bank, Washington, DC, 2017)
This paper makes the case for why safety nets are an important tool for managing the risk of natural hazards. The use of safety nets is advocated both ex ante, to prevent and mitigate the impact of natural disaster and ex post, to cope with the impacts of natural shocks. Firstly, the paper explores the implications of contextual factors to be taken into account in the design of an effective safety net system to respond to the needs generated by natural disasters. Learning from the responses to a number of recent natural disasters, a typology of the different types of natural hazards which require different approaches to reduce their risk is introduced. Secondly, the paper considers some 'guidelines' for improving the design and implementation of safety nets either to prevent and/or to recover from natural disasters. Finally, some conclusions and recommendations for more effective safety net and suggestions for addressing key issues are outlined.